Bioactive membranes for skin regeneration - Amaral, Katia Raquel Pereira (2024)
In recent years, biological organisms have been a source of inspiration for the development of nano- or micropatterned patches for applications in various medical fields. Within the various fabrication techniques of micro and nanoarchitectures, a soft lithography technique was used for the first time, in the fabrication of a new and optimized hydrogel-based patch with well-defined spaced micropillars. Based on the insights behind the biomimetics concept, a micropatterned patch derived from laminarin was developed, capable of capturing a large amount of drug particles, either in the powder form or encapsulated in alginate microspheres. This microstructure was inspired by the ability of honey bees to trap pollen grains between their body hair. Furthermore, to increase the adhesive capacity of the dressing, and inspired by the great adhesiveness of mussels, the laminarin, previously methacrylated for the purposes of crosslinking and hydrogel formation, was modified with catechol groups (ie hydroxypyridinone), allowing to increase the adhesiveness of the microfabricated dressing. Ciprofloxacin, a model antibiotic, was used to determine the release profile of two different systems: i) drug-powdered dressings or ii) drug-encapsulated alginate microparticles. The release profiles of the drug in both systems showed a rapid release of the drug in the first hours followed, by a controlled and sustained release over time, thus making these patches suitable for wound healing applications. Furthermore, cytotoxicity studies were performed, and the antimicrobial activity was verified. Overall, the results herein obtained suggest that our biocompatible patch could be implemented for wound regeneration, providing controlled and sustained delivery of high concentrations of drug, a moist environment and inherent antimicrobial activity that could solve the current problems associated with commercial medical dressings.